Synthesis and Characterization of Chitosan-Pectin-Citric Acid-Based Hydrogels for Biomedical Applications (Primary Wound Dressings) - Suryati Suryati; Rizka Mulyawan; Sulhatun Sulhatun; Muhammad Muhammad; Nikmat Wanda (Malikussaleh University, Aceh, Indonesia, 2023)
This study aims to analyze the processing of chitosan-pectin biocomposite hydrogel with the addition of citric acid to improve the quality of the biocomposite for primary wound dressing applications. The method is printing the biopolymer solution in a glass mold, then drying at 50oC. Chitosan 90.2% DD and pectin dissolved in 1% acetic acid with a ratio (w/w) of 50:50. The two ingredients were mixed using a magnetic stirrer at room temperature for 30 minutes until completely dissolved, then added citric acid crosslinking agent with various concentrations of 2,4, 6,8,10 (%). The test results for the characteristics of the chitosan-pectin-acid biocomposite Citrate obtained the best thickness in the composition variation (50:50:8) of 0.31 mm. The analysis results of the best absorption of the chitosan-pectin-citric acid biocomposite on the composition variation (50:50:6) were 185%. In the swelling analysis of the chitosan-pectin-citric acid biocomposite, the variation in composition (50:50:10) was 403%. The tensile strength test results of the chitosan-pectin-citric acid biocomposite decreased with the addition of citric acid, the best obtained was 20.76 MPa, and the best elongation was 76.0%. Test results for the functional group of the chitosan-pectin-CaCl2 biocomposite for the presence of O-H, C-H, N-H bonds in the fact of O-H, C-H, N-H bonds at a wavelength of 4000-2500 cm-1, C=O, C=N, C=C at a wavelength of 2000 -1500, and the specific absorption of the chitosan-pectin-citric acid biocomposite 400-1400 cm-1 indicates that the resulting membrane tends to be polar, hydrophilic and environmentally friendly because it can be degraded. Based on the expected test results, it was shown that the chitosan-pectin-CaCl2 biocomposite has the potential to be applied as an ideal primary wound dressing for wound healing and protection.